Ascetic passions: emotions in early Christian Egypt - Crislip, Andrew T. (Critical approaches to early Christianity, 2026)
"Ascetic Passions: Emotions in Early Christian Egypt reveals the role of emotions in shaping early Christian theology, community, and monastic practices in Egypt. Drawing from biblical interpretation, theological treatises, and Coptic monastic and apocryphal literature, Crislip explores how emotions such as envy, anger, sadness, and joy influenced Christian life and thought. The book highlights how early Christians saw emotions as both spiritual challenges and tools for moral growth. Discussions of figures like Evagrius of Pontus and Shenoute showcase how emotional regulation, community, and identity were central to monastic life. The volume offers new insights into the emotional landscape of late antiquity"-- Provided by publisher